Study of electrophysical processes and aging of the material of highvoltage insulators to determine their working life - D. A. Ivanov (Известия высших учебных заведений: Проблемы энергетики)
The article is aimed to discuss the results of research on the characteristics of partial discharges on defects of different types in high-voltage insulators - on dielectric rod and contact «terminal rod». The atypical characteristics of partial discharges in high-voltage insulators were analysed using an original method of determining their condition using a set of diagnostic parameters.METHODS. Experimental results are obtained by electromagnetic and acoustic methods of non-contact measurements of partial discharge characteristics.THE RESULTS of conducted studies are obtained circuits of electrophysical processes in dielectric cavities of defects at dielectric rod and contact «terminal rod» during one period of high voltage application. The circuit of electrophysical processes takes into account changes of the field induced by partial discharges in the defect cavity and on its dielectric surfaces.CONCLUSHIONS. The main conclusion is the fact that the developed scheme of generation of conventional and powerful partial discharges found confirmation in the model of the process of generation and subsequent distribution of primary discharge in the defect cavity. Under real conditions of partial discharge radiation in polymer and porcelain high-voltage insulators is more complex, so the first attempt to explain the generation of powerful partial discharges in real high-voltage power systems was made. The increase in the number of partial discharges and their intensity during the phase interval of 20° and the presence of powerful partial discharges are the main signs of defective high-voltage insulators.